2017
DOI: 10.1101/118380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional asymmetry in the central brain regions in boys with Attention Deficit Hyperactivity Disorder detected by Event Related Potentials during performance of the Attentional Network Test

Abstract: Background: Various functional asymmetries detected by different neurophysiological and neuroimaging methods have been reported in the literature on the Attention Deficit Hyperactivity Disorder (ADHD), some of them pointing to the right hemisphere activity. In our attempt to discriminate the ADHD patients from normal subjects by hierarchical clustering of behavioural, psychological and event related potential (ERP) variables, the late P3 component of potentials from the right central region (C4) proved to be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In this pool, the most informative neurophysiological variables proved to be topographically asymmetrical and represent the binded information from parietal and frontal regions linked to right frontal sites and the early (45 to 290ms after target) 'C3 minus C4' asymmetry. This asymmetry has already been shown to correlate with DSM scores, mainly with hyperactivity/impulsivity (32). Our results are evidence that some people could be biologically classified as "inattentive and hyperactive".…”
Section: Discussionsupporting
confidence: 74%
“…In this pool, the most informative neurophysiological variables proved to be topographically asymmetrical and represent the binded information from parietal and frontal regions linked to right frontal sites and the early (45 to 290ms after target) 'C3 minus C4' asymmetry. This asymmetry has already been shown to correlate with DSM scores, mainly with hyperactivity/impulsivity (32). Our results are evidence that some people could be biologically classified as "inattentive and hyperactive".…”
Section: Discussionsupporting
confidence: 74%
“…The P3 wave, a late potential related to cognitive tasks (Hruby & Marsalek, 2003) is particularly sensitive to ADHD conditions (Barry, Johnstone & Clarke, 2003; Kratz et al, 2011), which justifies the importance of cue- and target-related late potentials in classification, mainly in the mid-parietal region where this wave is most pronounced. In a recent study, we found an ERP asymmetry (from 45 to 290 ms after target onset) in the ‘C3 minus C4’ channel, which was shown to correlate with ADHD phenomenology (Abramov et al, 2016). Several studies have shown brain asymmetries related to ADHD phenomenology, especially in the frontal-striatal network (Barkley, 1997; Barkley, 2006; Langleben et al, 2001; Dang et al, 2016).…”
Section: Discussionmentioning
confidence: 90%